Nutrient Requirements of Laboratory Animals,: Fourth Revised Edition, 1995 - National Research Council (The National Academies Press, 1995)
In the years since the third edition of this indispensable reference was published, a great deal has been learned about the nutritional requirements of common laboratory species: rat, mouse, guinea pig, hamster, gerbil, and vole. The Fourth Revised Edition presents the current expert understanding of the lipid, carbohydrate, protein, mineral, vitamin, and other nutritional needs of these animals. The extensive use of tables provides easy access to a wealth of comprehensive data and resource information. The volume also provides an expanded background discussion of general dietary considerations. In addition to a more user-friendly organization, new features in this edition include: A significantly expanded section on dietary requirements for rats, reporting substantial new findings. A new section on nutrients that are not required but that may produce beneficial results. New information on growth and reproductive performance among the most commonly used strains of rats and mice and on several hamster species. An expanded discussion of diet formulation and preparation—including sample diets of both purified and natural ingredients. New information on mineral deficiency and toxicity, including warning signs. This authoritative resource will be important to researchers, laboratory technicians, and manufacturers of laboratory animal feed.
Keywords: Biology and Life Sciences; Agriculture

The Role of Technology in Environmentally Sustainable Development (The National Academies Press, 1995)
Keywords: Environment and Environmental Studies

An Assessment of Continued R & D into an Electrometallurgical Approach for Treating DOE Spent Nuclear Fuel (The National Academies Press, 1995)
Keywords: Environment and Environmental Studies

Earth Observations From Space: History, Promise, and Reality (Executive Summary) (The National Academies Press, 1995)
Keywords: Space and Aeronautics

Airborne Geophysics and Precise Positioning: Scientific Issues and Future Directions - National Research Council (The National Academies Press, 1995)
The Global Positioning System, with its capability for both precisely positioning and navigating an aircraft, has created new scientific opportunities for studying the earth. This book examines the state of the art in airborne geophysics as integrated with new precise positioning systems, and it outlines the scientific goals of focused effort in airborne geophysics, including advances in our understanding of solid earth processes, global climate change, the environment, and resources.
Keywords: Earth Sciences; Space and Aeronautics

Wetlands: Characteristics and Boundaries - National Research Council (The National Academies Press, 1995)
"Wetlands" has become a hot word in the current environmental debate. But what does it signify? In 1991, proposed changes in the legal definities of wetlands stirred controversy and focused attention on the scientific and economic aspects of their management. This volume explores how to define wetlands. The committee—whose members were drawn from academia, government, business, and the environmental community—builds a rational, scientific basis for delineating wetlands in the landscape and offers recommendations for further action. Wetlands also discusses the diverse hydrological and ecological functions of wetlands, and makes recommendations concerning so-called controversial areas such as permafrost wetlands, riparian ecosystems, irregularly flooded sites, and agricultural wetlands. It presents criteria for identifying wetlands and explores the problems of applying those criteria when there are seasonal changes in water levels. This comprehensive and practical volume will be of interest to environmental scientists and advocates, hydrologists, policymakers, regulators, faculty, researchers, and students of environmental studies.
Keywords: Environment and Environmental Studies

Building a North American Feed Information System (The National Academies Press, 1995)
Keywords: Agriculture

High-Purity Chromium Metal: Supply Issues for Gas-Turbine Superalloys (The National Academies Press, 1995)
Keywords: Engineering and Technology

Recommendations for Research on the Health of Military Women: Bibliographies - Institute of Medicine (The National Academies Press, 1995)
Keywords: Health and Medicine

Coal: Energy for the Future - National Research Council (The National Academies Press, 1995)
The U.S. Department of Energy (DOE) was given a mandate in the 1992 Energy Policy Act (EPACT) to pursue strategies in coal technology that promote a more competitive economy, a cleaner environment, and increased energy security. Coal evaluates DOE's performance and recommends priorities in updating its coal program and responding to EPACT. This volume provides a picture of likely future coal use and associated technology requirements through the year 2040. Based on near-, mid-, and long-term scenarios, the committee presents a framework for DOE to use in identifying R&D strategies and in making detailed assessments of specific programs. Coal offers an overview of coal-related programs and recent budget trends and explores principal issues in future U.S. and foreign coal use. The volume evaluates DOE Fossil Energy R&D programs in such key areas as electric power generation and conversion of coal to clean fuels. Coal will be important to energy policymakers, executives in the power industry and related trade associations, environmental organizations, and researchers.
Keywords: Energy and Energy Conservation

Aviation Weather Services: A Call For Federal Leadership and Action - National Research Council (The National Academies Press, 1995)
Each time we see grim pictures of aircraft wreckage on a rain-drenched crash site, or scenes of tired holiday travelers stranded in snow-covered airports, we are reminded of the harsh impact that weather can have on the flying public. This book examines issues that affect the provision of national aviation weather services and related research and technology development efforts. It also discusses fragmentation of responsibilities and resources, which leads to a less-than-optimal use of available weather information and examines alternatives for responding to this situation. In particular, it develops an approach whereby the federal government could provide stronger leadership to improve cooperation and coordination among aviation weather providers and users.
Keywords: Earth Sciences; Space and Aeronautics

A Data Foundation For The National Spatial Data Infrastructure (The National Academies Press, 1995)
Keywords: Earth Sciences

Ward Valley: An Examination of Seven Issues in Earth Sciences and Ecology - National Research Council (The National Academies Press, 1995)
The book examines specific scientific and technical safety issues related to the proposed low-level radioactive waste site at Ward Valley, California. It includes, among other issues, evaluation of the potential for infiltration by shallow subsurface water, contamination of ground water and the Colorado River, damaging effects on the desert tortoise habitat, and restoration of the native vegetation.
Keywords: Environment and Environmental Studies; Earth Sciences

Understanding Marine Biodiversity - National Research Council (The National Academies Press, 1995)
The diversity of marine life is being affected dramatically by fishery operations, chemical pollution and eutrophication, alteration of physical habitat, exotic species invasion, and effects of other human activities. Effective solutions will require an expanded understanding of the patterns and processes that control the diversity of life in the sea. Understanding Marine Biodiversity outlines the current state of our knowledge, and propose research agenda on marine biological diversity. This agenda represents a fundamental change in studying the ocean—emphasizing regional research across a range of space and time scales, enhancing the interface between taxonomy and ecology, and linking oceanographic and ecological approaches. Highlighted with examples and brief case studies, this volume illustrates the depth and breadth of undescribed marine biodiversity, explores critical environmental issues, advocates the use of regionally defined model systems, and identifies a series of key biodiversity research questions. The authors examine the utility of various research approaches—theory and modeling, retrospective analysis, integration of biotic and oceanographic surveys—and review recent advances in molecular genetics, instrumentation, and sampling techniques applicable to the research agenda. Throughout the book the critical role of taxonomy is emphasized. Informative to the scientist and accessible to the policymaker, Understanding Marine Biodiversity will be of specific interest to marine biologists, ecologists, oceanographers, and research administrators, and to government agencies responsible for utilizing, managing, and protecting the oceans.
Keywords: Biology and Life Sciences; Earth Sciences

Effects of Past Global Change on Life - National Research Council (The National Academies Press, 1995)
What can we expect as global change progresses? Will there be thresholds that trigger sudden shifts in environmental conditions—or that cause catastrophic destruction of life? Effects of Past Global Change on Life explores what earth scientists are learning about the impact of large-scale environmental changes on ancient life—and how these findings may help us resolve today's environmental controversies. Leading authorities discuss historical climate trends and what can be learned from the mass extinctions and other critical periods about the rise and fall of plant and animal species in response to global change. The volume develops a picture of how environmental change has closed some evolutionary doors while opening others—including profound effects on the early members of the human family. An expert panel offers specific recommendations on expanding research and improving investigative tools—and targets historical periods and geological and biological patterns with the most promise of shedding light on future developments. This readable and informative book will be of special interest to professionals in the earth sciences and the environmental community as well as concerned policymakers.
Keywords: Environment and Environmental Studies; Earth Sciences

Education of Architects and Engineers for Careers in Facility Design and Construction (The National Academies Press, 1995)

Prudent Practices in the Laboratory: Handling and Disposal of Chemicals - National Research Council (The National Academies Press, 1995)
This volume updates and combines two National Academy Press bestsellers—Prudent Practices for Handling Hazardous Chemicals in Laboratories and Prudent Practices for Disposal of Chemicals from Laboratories—which have served for more than a decade as leading sources of chemical safety guidelines for the laboratory. Developed by experts from academia and industry, with specialties in such areas as chemical sciences, pollution prevention, and laboratory safety, Prudent Practices for Safety in Laboratories provides step-by-step planning procedures for handling, storage, and disposal of chemicals. The volume explores the current culture of laboratory safety and provides an updated guide to federal regulations. Organized around a recommended workflow protocol for experiments, the book offers prudent practices designed to promote safety and it includes practical information on assessing hazards, managing chemicals, disposing of wastes, and more. Prudent Practices for Safety in Laboratories is essential reading for people working with laboratory chemicals: research chemists, technicians, safety officers, chemistry educators, and students.
Keywords: Math, Chemistry, and Physics; Environment and Environmental Studies

Not Eating Enough: Overcoming Underconsumption of Military Operational Rations - Institute of Medicine (The National Academies Press, 1995)
Eating enough food to meet nutritional needs and maintain good health and good performance in all aspects of life—both at home and on the job—is important for all of us throughout our lives. For military personnel, however, this presents a special challenge. Although soldiers typically have a number of options for eating when stationed on a base, in the field during missions their meals come in the form of operational rations. Unfortunately, military personnel in training and field operations often do not eat their rations in the amounts needed to ensure that they meet their energy and nutrient requirements and consequently lose weight and potentially risk loss of effectiveness both in physical and cognitive performance. This book contains 20 chapters by military and nonmilitary scientists from such fields as food science, food marketing and engineering, nutrition, physiology, psychology, and various medical specialties. Although described within a context of military tasks, the committee's conclusions and recommendations have wide-reaching implications for people who find that job-related stress changes their eating habits.
Keywords: Health and Medicine; Food and Nutrition

A Review of Two Hanford Environmental Dose Reconstruction Project (HEDR) Dosimetry Reports: Columbia River Pathway and Atmospheric Pathway (The National Academies Press, 1995)
Keywords: Environment and Environmental Studies

Consideration of the Nutrition Components of the Sick Child Initiative - Institute of Medicine (The National Academies Press, 1995)
Keywords: Health and Medicine